A Mechanochromic Single Crystal: Turning Two Color Changes into a Tricolored Switch. Issue 2 (24th November 2015) - Ma, Zhiyong; Wang, Zhijian; Meng, Xiao; Ma, Zhimin; Xu, Zejun; Ma, Yuguo; Jia, Xinru
Abstract: The single crystal of M‐4‐B was obtained by attaching the boron of BH3 to the amine linker between a tetraphenylethylene (TPE) unit and rhodamine B. M‐4‐B showed a novel sequential tricolor switching from dark blue to bluish‐green and to a reddish color upon grinding. The boron atom played a key role in developing the single crystal. Abstract : Tricolor switch : A single crystal of M‐4‐B was obtained by attaching the boron of BH3 to the amine linker between a tetraphenylethylene unit and rhodamine B. M‐4‐B showed a novel sequential tricolor switching from deep‐blue to bluish‐green and to a reddish color upon grinding. The boron atom played a key role in obtaining the single crystal (see picture: O red, N blue, B yellow).